Carbon nanotubes: their potential and pitfalls for bone tissue regeneration and engineering - Newman, Peter; Minett, Andrew; Ellis-Behnke, Rutledge; Zreiqat, Hala (Nanomedicine. Nanotechnology, biology and medicine, 2013)
The extracellular environment which supports cell life is composed of a hierarchy of maintenance, force and regulatory systems which integrate from the nano- through to macroscale. For this reason, strategies to recreate cell supporting environments have been investigating the use of nanocomposite biomaterials. Here, we review the use of carbon nanotubes as part of a bottom-up approach for use in bone tissue engineering. We evaluate the properties of carbon nanotubes in the context of synthetic tissue substrates and contrast them with the nanoscale features of the extracellular environment. Key studies are evaluated with an emphasis on understanding the mechanisms through which carbon nanotubes interact with biological systems. This includes an examination of how the different properties of carbon nanotubes affect tissue growth, how these properties and variation to them might be leveraged in regenerative tissue therapies and how impurities or contaminates affect their toxicity and biological interaction. - From the Clinical Editor - In this comprehensive review, the authors describe the status and potential applications of carbon nanotubes in bone tissue engineering.
Gesehen am 24.01.2022